Phytochemistry and Antiviral Properties of Two Lotus Species ‎Growing in Egypt - Ahmed Mohamed Mohamed Youssef; Zeinb Ahmad Said EL-Swaify EL-Swaify; Doaa Ahmed ‎Mohamed Maaty; Mohamed Mohamed Youssef (Vitae, 2022)
Background: Lotus arabicus L and Lotus glaber Mill. belong to the family Fabaceae, and they grow in the wild in ‎Egypt and have different therapeutic uses in folk medicine. Objectives: This study aimed to evaluate the phytochemical profile and ‎antimicrobial properties of the methanolic extracts of two Lotus spp. growing in Egypt, L. ‎arabicus and L. glaber. Material and methods: Gas chromatography-mass spectrometry was used to identify the compounds of the extracts of two Lotus species. An MTT colorimetric assay and the disc diffusion method were performed to investigate the antiviral and antimicrobial activities of two lotus species, respectively. Results: The n-hexane and methanol extracts of L. ‎arabicuscontained high percentages of alkane hydrocarbons, such as 5-methyloctadecane, ‎while L. glaber contained dodecane. The major compounds in the methanol extract of L. ‎arabicus were hexadecanoic acid methyl ester and dodecanoic acid,2,3-bis(acetyloxy)propyl ‎ester. The major compounds in the methanol extract of L. glaber were palmitic acid and ‎lucenin 2. The indole alkaloid ditaine was found only in L. arabicus. This alkaloid was ‎identified for the first time in the genus Lotus. The antimicrobial properties of the extracts of ‎the two Lotus species showed that the n-hexane extract of ‎both Lotus species may have potential antifungal activity against Candida parapsilosis and ‎Aspergillus flavus. Moreover, the methanolic extracts of both Lotus species have potential ‎antiviral activity against the coxsackie B virus, but only the L. arabicus extract showed ‎activity against the hepatitis A virus.‎ Conclusion: Lotus arabicus might have potential antifungal or antiviral activity greater than L. glaber.